Download presentation

Presentation is loading. Please wait.

Published byMyah Holtby Modified about 1 year ago

1
Starter Revision Worksheet

2
Note 6: Expanding Brackets One Bracket: Multiply the outside term by everything inside the brackets Simplify if possible Examples: -4(x + 3) = x(3x – 6) =-4x x 2 – 6x 4(3x – 5) – 2(7 – x) = 12x - 20 – x = 14x - 34

3
Two Bracket (Quadratics): Everything in the first bracket gets multiplied with everything in the second bracket Examples: (x + 3)(x – 6)= x 2 - 6x + 3x - 18 = x 2 – 3x - 18 (2x – 5)(3 – x) = 6x – 2x 2 – x = -2x x - 15

4
A perfect square has both brackets the same Example: (x + 9) 2 = x 2 + 9x + 9x + 81 = x x + 81 (x – 5)(x + 5) = x 2 + 5x – 5x - 25 = x = (x + 9)(x + 9) The difference of two squares has two brackets the same except for the signs (+ or -), when expanded there will be no middle term

5
Page 45 Exercise G and H

Similar presentations

© 2016 SlidePlayer.com Inc.

All rights reserved.

Ads by Google